Philippe Lambin: how advances in imaging impact precision radiation oncology? - Wang, Julia (Precision Cancer Medicine; Vol 1 (September 2018): Precision Cancer Medicine, 2018)
The 10th Shanghai International Conference on Radiation Oncology was held during August 10–11, 2018 in Shanghai, China. The conference was attended by numerous internationally renowned experts, devoting much attention to thoracic tumor radiotherapy and covering dozens of international academic researches.